ASSESSMENT OF FISH-BIODIVERSITY OF KOYA KUJIYA BEEL, ABHAYAPURI, ASSAM IN RELATION TO CERTAIN PHYSICOCHEMICAL AND ANTHROPOGENIC FACTORS - CH. KALITA, JOGEN; URMIMALA SARMA DEKA,; ANSARUL HAQUE,; CH. KALITA, TAPAN (The Bioscan, 2011)
The present study for the first time examined the fish diversity status of the Koya Kujiya Beel in the Goalpara district of Assam (North-East India). The study investigated the parameters related to the physico-chemical nature of the beel and found that the Koya Kujia Beel has been losing its physical and productive life due to different anthropogenic activities. The study recorded 31 species and 25 genera of zooplankton belonging to four classes namely Protozoa, Rotifera, Copepoda and Cladocera. Phytoplankton diversity in the beel was also found to be very rich. During the study period (summer season) 13,440 number per litre were recorded, of which 50.55% Chlorophyceae, 48.82% Myxiphyceae and only 0.63% were Bacillariophyceae. Altogether 12 different species of phytoplankton recorded during the study period in the beel. In the present investigation a total of 45 species of fishes were identified of which 10 species fall under major group, 13 species fall under intermediate group and 22 species fall under minor group. The present study established that most of the physico-chemical and biological attributes provide congenial environment for fish growth in the beel. The fish catch statistics revealed that the population status of the fish species has been found to be gradually declining.